A Novel Pyroptosis-Associated Long Non-coding RNA Signature Predicts Prognosis and Tumor Immune Microenvironment of Patients With Breast Cancer - Ping, Liqin; Zhang, Kaiming; Ou, Xueqi; Qiu, Xingsheng; Xiao, Xiangsheng (Frontiers in Cell and Developmental Biology, 2021)
Background: Pyroptosis, an inflammatory form of programmed cell death, plays an important role in the occurrence and development of cancer. However, few studies focus on the pyroptosis-associated long non-coding RNAs (lncRNAs) in breast cancer (BC). The prognostic value of pyroptosis-associated lncRNAs and their relationship with tumor microenvironment (TME) in BC remain unclear. The purpose of this article is to explore the prognostic role of pyroptosis-associated lncRNAs and their relationship with TME in BC. Methods: The transcriptome data and clinical data of female BC patients were downloaded from TCGA database. 937 patients were randomly divided into training set or validation set. A pyroptosis-associated lncRNAs signature was constructed with the training set and verified in the validation set. Functional analysis and immune microenvironment analysis related to pyroptosis-associated lncRNAs were performed. A nomogram including the risk score and clinical characteristics was established. Results: A 9-pyroptosis-associated lncRNAs signature was constructed to separate BC patients into two risk groups. High-risk patients had poorer prognosis than low-risk patients. The risk score was proved to be an independent prognostic factor by multivariate Cox regression analysis. Function analysis and immune microenvironment analysis showed that low-risk BC patients tended to be immunologically “hot” tumor. A nomogram was constructed with risk score and clinical characteristics. Receiver operating characteristic curve (ROC) analysis demonstrated credible predictive power of the nomogram. The area under time-dependent ROC curve (AUC) reached 0.880 at 1-year, 0.804 at 3-year, 0.769 at 5-year in the training set and 0.799 at 1-year, 0.794 at 3-year, 0.728 at 5-year in the validation set. Conclusion: We identified a novel pyroptosis-associated lncRNAs signature which was an independent prognostic indicator for BC patients. Pyroptosis-associated lncRNAs had potential relationship with immune microenvironment and might be therapeutic targets for BC patients.